Illuminating the secrets of crystals: microcrystal electron diffraction in structural biology. (6th February 2019) - Barringer, Rob
Abstract: X-ray crystallography (XRC) has visualised biological macromolecules in exquisite detail for over 50 years, relying on a combination of mathematical principles to offer insight into atomic structures. Crystals can diffract various electromagnetic waves aside from the conventional X-ray, offering an alternative approach to crystallographic structural analysis. Microcrystal electron diffraction (MicroED) illuminates crystals with electron waves instead of X-rays. Two specialised groups have demonstrated that MicroED can give high-resolution (often atomic) data, and now appears to be developing into a powerful alternative method to XRC or electron microscopy of macromolecules. How MicroED compares to XRC will be key to assessing it as a stand-alone crystallographic technique. This review presents a critical analysis of MicroED, with comments on theoretical and practical aspects and suggestions of further work and development.